Acquisition of Host Cell DNA Sequences by Baculoviruses: Relationship Between Host DNA Insertions and FP Mutants of Autographa californica and Galleria mellonella Nuclear Polyhedrosis Viruses - Fraser, M. J. (1983)
Mutants of Autographa californica and Galleria mellonella nuclear polyhedrosis viruses, which produce an altered plaque phenotype as a result of reduced numbers of viral occlusions in infected cells, were isolated after passage in Trichoplusia ni (TN-368) cells. These mutants, termed FP (few-polyhedra) mutants, had acquired cell DNA sequences ranging from 0.8 to 2.8 kilobase pairs in size. The insertions of cell DNA occurred in a specific region between 35.0 and 37.7 map units of the A. californica viral genome. A cloned viral fragment containing one of the host DNA inserts was homologous to host DNA inserts in two other mutant viruses and to dispersed, repetitious sequences in T. ni cell DNA. Most of the homology between the cloned insert and cell DNA was contained within a 1,280-base-pair AluI fragment. Marker rescue studies and analysis of infected-cell-specific proteins suggested that the insertion of cell DNA into the viral genomes resulted in the FP plaque phenotype, possibly through the inactivation of a 25,000-molecular-weight protein.